Dataset for Understanding and designing post-build rolling for mitigation of residual stress and distortion in wire arc additively manufactured components - Gornyakov, Valeriy; Ding, Jialuo; Sun, Yongle; Williams, Stewart W. (Cranfield University, 2022)
Dataset for Figure 9 Influence of friction coefficient on longitudinal PS in the WAAM built component after rolling: a) flat roller, b) profiled roller, and c) slotted roller (F = 50 kN). Dataset for Figure 10 Vertical penetration of slotted roller for different friction coefficients (F = 50 kN). Dataset for Figure 11 Influence of friction coefficient on longitudinal RS distributions in the WAAM built component after rolling with a) flat roller, b) profiled roller and c) slotted roller (F = 50 kN). Dataset for Figure 13 Influence of rolling load on longitudinal PS in the WAAM component after rolling: a) flat roller, b) profiled roller, and c) slotted roller (µ = 0.1). Dataset for Figure 15 Influence of rolling load on the longitudinal RS in the WAAM component after rolling: a) flat roller, b) profiled roller, and c) slotted roller (µ = 0.1). Dataset for Figure 16 Influence of roller design on mitigation of the compressive longitudinal PS caused by WAAM deposition. The rolling loads are a) 25 kN, b) 50 kN and c) 75 kN (µ = 0.1). Dataset for Figure 17 Influence of roller design on mitigation of the tensile longitudinal RS caused by WAAM deposition. The rolling loads are a) 25 kN, b) 50 kN, and c) 75 kN (µ = 0.1). Dataset for Figure 19 Influence of the post-build rolling using the flat roller on the WAAM deposition RS obtained by the long mechanical model before and after clamps removal (F = 50 kN and µ = 0.1). Dataset for Figure 20 Comparison of vertical distortion in as-built and post-build rolled full-length WAAM component after removal of clamps (flat roller, F = 50 kN and µ = 0.1). Dataset for Figure 21 Comparison of vertical distortion in long WAAM components after post-build rolling with flat, profiled and slotted rollers at rolling loads of a) 25 kN, b) 50 kN, and c) 75 kN (µ = 0.1). Dataset for Figure 22 Comparison in a) PS and b) RS predictions between flat roller models with and without consideration of the WAAM deposition before rolling simulation (µ = 0.5).
Keywords: 'Directed Energy Deposition'; 'Cold Working'; 'Residual stresses'; 'Plastic Deformation'; 'Roller Geometry'; 'Rolling Load'; 'Manufacturing Processes and Technologies (excl. Textiles)'